2018
DOI: 10.1097/iop.0000000000001164
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin and Pembrolizumab Chemoimmunotherapy Achieves Remission in Recurrent, Metastatic Sebaceous Carcinoma

Abstract: A 72-year-old Caucasian woman who had recurrent sebaceous carcinoma of the right orbit with bilateral cervical lymph node involvement 24 months after orbital exenteration was treated with carboplatin (area under the curve of 5) and pembrolizumab (2 mg/kg) for 6 cycles, followed by maintenance pembrolizumab. She obtained a complete pathological remission and remains free of local, regional, and systemic disease at 15 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 12 publications
0
19
0
1
Order By: Relevance
“…The patient in this report likely responded to pembrolizumab as a result of the MSI-H status of the tumor, whereas the patient in the report by Domingo-Musibay et al 8 likely responded as a result of high TMB. The patient reported by Kodali et al 9 is interesting in that the tumor characteristics (MSI low, PD-L1 low) would generally predict little benefit from immunotherapy. However, the use of chemotherapy first may increase tumor antigen expression via cell death, thereby priming the tumor for response to subsequent immunotherapy.…”
Section: Context Key Objectivementioning
confidence: 97%
See 1 more Smart Citation
“…The patient in this report likely responded to pembrolizumab as a result of the MSI-H status of the tumor, whereas the patient in the report by Domingo-Musibay et al 8 likely responded as a result of high TMB. The patient reported by Kodali et al 9 is interesting in that the tumor characteristics (MSI low, PD-L1 low) would generally predict little benefit from immunotherapy. However, the use of chemotherapy first may increase tumor antigen expression via cell death, thereby priming the tumor for response to subsequent immunotherapy.…”
Section: Context Key Objectivementioning
confidence: 97%
“…Kodali et al 9 reported a 72-year-old woman with recurrent sebaceous carcinoma of the right orbit treated with chemotherapy and immunotherapy. The patient initially received 1 cycle of carboplatin but experienced rapid progression.…”
Section: Context Key Objectivementioning
confidence: 99%
“…Anti-PD1 checkpoint inhibitor pembrolizumab has had anecdotal success in two cases of metastatic sebaceous carcinoma. 49,50…”
Section: Immunotherapymentioning
confidence: 99%
“…73,107 In two case reports, the use of pembrolizumab with or without chemotherapy demonstrated clinical efficacy against metastatic sebaceous carcinoma. 108,109 One patient remained on pembrolizumab despite requiring systemic corticosteroids due to secondary adrenal insufficiency. 108…”
Section: Cutaneous Adnexal Carcinomasmentioning
confidence: 99%